Struktury hybrydowe w organizacjach procesowych - Krzos, Grzegorz (Hybrid Structures in Process Organizations, 2009)
In this paper reasons for hybrid approach in organizational structures projecting were described. There are lots of examples of hybrid structures in Polish enterprises and local governments. It seems that hybrid approaches are examples of positive reactions of organizations to the changing environments inside and outside their organizations. Observations show that traditional types of structures described in the literature are not the only one in today's organizations. Nowadays, many organizations use hybrid structures during implementation of process organization. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 396-403